ANALISIS PROSES COLLABORATIVE GOVERNANCE DALAM MENANGGULANGI BENCANA BANJIR DI KOTA SEMARANG - Latifah, Hazimah; Nurcahyanto, Herbasuki; Marom, Aufarul (Journal of Public Policy and Management Review, 2024)
Flood management cannot be carried out by one agency or institution alone, so there needs to be cooperation between stakeholders in order to create joint synergy in dealing with flood problems. This proves that it is necessary to implement Collaborative Governance to simplify and speed up the handling of flood problems. However, in its implementation there are still problems that show that collaboration in flood disaster management in the city of Semarang has not been optimal. The aim of this research is to analyze the Collaborative Governance process in overcoming flood disasters in Semarang City and identify factors inhibiting the implementation of the Collaborative Governance process in overcoming flood disasters in Semarang City. The method used is descriptive qualitative with data collection techniques through interviews, observation, documentation and literature study. The research results show that the Collaborative Governance process in overcoming the flood disaster in Semarang City has gone well through several stages including face to face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes, although there are still obstacles. In the collaboration process there are inhibiting factors that can cause failure in a collaboration, namely cultural factors, institutional factors and political factors. Each collaborative actor has built communication and coordination with all parties involved in overcoming the flood disaster in Semarang City. However, there are still obstacles such as several non-government agencies that do not yet have a forum for communication. Therefore, in implementing collaborative flood disaster management in the city of Semarang, it is necessary to have a communication platform to move one door in order to facilitate communication between